EXPERIMENTAL CHECK OF EFFECTIVE MANAGEMENT OF LINKS OF GAS AND SMOKE PROTECTIVE SERVICE AT INTRODUCTION OF SENSORS OF A MOTIONLESS STATE - E. N. Tuzhikov (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives The environmental factors at the fire that affect the efficiency of the operational activities of fire and rescue units in an unfit environment for breathing and statistical information on the functioning of the gas and smoke protection service in regions of the Russian Federation are given. Method The methodology for conducting experiments with groups of reconnaissance to search for an injured firefighter is given. A description of the location of the experiment and the algorithm for the movement of reconnaissance groups are presented. Result Results of experiments on the actions of the units of gas and smoke protective service inside fire object on search of the injured firefighter who is in unconsciousness are given. The experiment was conducted in the conditions of premises without lighting and with influence of noise hindrances to staff of groups of reconnaissance. The results of the experiments confirm the need of identification of firefighters at the site of a fire by of sensors of a motionless state and light reflecting elements of clothes and equipment. The results of the experiments are correlated with previously conducted experiments to study the time of fire reconnaissance in the premises of residential and public buildings. The necessity of the research of the parameters of the work of groups of reconnaissance at various sites on the basis of the temporal parameters of the work of gas and smoke defenders has been determined. Conclusion The positive influence of the presence factor of immobile sensors in the personnel of fire and rescue units operating in conditions unsuitable for breathing environment has been established. The proposed directions for the research of organizational systems for the management of fire departments at the fire.